METHODOLOGY OF SCIENTIFIC AND PRACTICAL RESEARCH TO IMPROVE MILITARY SCIENCE IN MODERN SOCIETY (Scientific journal of the Fergana State University, 2026)
This article examines the changes occurring in the paradigm of military science in modern society and the methodology of the research conducted. Geopolitical conflicts and wars in the global military-political arena require modernization of the paradigm of military science, creating the need to strengthen innovative military-scientific research. Modern military science, going beyond the classical military strategy, requires the development of science, embracing new scientific theories and applied research through updating the methodological approach. Scientific and applied research conducted in modern military science, in turn, is developed on the basis of transdisciplinary approaches that require interdisciplinary integration. Consequently, military-scientific research not only strengthens strategic, tactical or technical sciences, but also strengthens the social and humanitarian sciences, including interdisciplinary approaches integrated with cognitive sciences, social psychology, epistemology.